1995
DOI: 10.1007/bf00383718
|View full text |Cite
|
Sign up to set email alerts
|

Spinal tumors and subarachnoid hemorrhage: pathogenetic and diagnostic aspects in 5 cases

Abstract: The authors report 5 cases of spinal tumor associated with subarachnoid hemorrhage. Histologically, the tumor was an ependymoma in 2 cases, a neurinoma in 2 cases and a hemangioblastoma in 1 case. The pathogenetic and diagnostic characteristics of these 5 cases are analyzed in the light of other published reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 15 publications
0
21
1
Order By: Relevance
“…16) Only 17 cases of hemangioblastoma associated with SAH have been reported 2,3,5,6,8,9,13,16,18,20,21,27,29) (Table 1). The characteristic symptoms of spinal SAH are severe pain along the spinal axis (neck pain and back pain/lumbago), radicular pain, paresis originating at the spinal roots, 16) or myelopathy, as seen in our present patient.…”
Section: Discussionmentioning
confidence: 99%
“…16) Only 17 cases of hemangioblastoma associated with SAH have been reported 2,3,5,6,8,9,13,16,18,20,21,27,29) (Table 1). The characteristic symptoms of spinal SAH are severe pain along the spinal axis (neck pain and back pain/lumbago), radicular pain, paresis originating at the spinal roots, 16) or myelopathy, as seen in our present patient.…”
Section: Discussionmentioning
confidence: 99%
“…First theory is a mechanical cause 1,5) . Cervoni et al 1) reported that 79% of the 63 tumors associated with SAH were situated in the region of the filum terminale and medullary conus and even thought tumors of this region account for only 20% of spinal tumors and the acute onset of SAH after physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Cervoni et al 1) reported that 79% of the 63 tumors associated with SAH were situated in the region of the filum terminale and medullary conus and even thought tumors of this region account for only 20% of spinal tumors and the acute onset of SAH after physical exercise. Movements of traction along the spine column involving the cervical region may stretch the most superficial portion of the tumor including its vascular connections with the adjacent structures, especially when traction is repeated and prolonged 1) . Such tractional force occur most commonly in areas of high mobility, and this probably explains why the onset of symptoms in 50% of cases is related to exertion 7,9) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations